2018 UBT International Conference 2018
DOI: 10.33107/ubt-ic.2018.315
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneurship and Strategic Management in Kosovo SME Sector

Abstract: This paper examines the impact of Entrepreneurship and Strategic Management Activities in SME sector in Kosovo. The subject was developed based on a broad literature and practices in the SME development sector, and the great importance of strategic activities in regards of firms' growth. While preparing the paper, various methods were utilized for researching and studying strategic economic development, with the focal points in SME development. It is well known that the purpose of strategic development for Ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The sampling technique used for this research was the convenience sampling technique due to the fact that the study focuses only on the behaviour of s-commerce purchasers. Regarding the demographic distribution of population and the sample design, the authors referred to reports of the Kosovo Agency of Statistics (Krasniqi et al, 2018) and Albania Institute of Statistics (2019). After data gathering, 721 valid questionnaires from Kosovo and Albania were used for further analysis.…”
Section: Data Collection Procedures and Research Methodologymentioning
confidence: 99%
“…The sampling technique used for this research was the convenience sampling technique due to the fact that the study focuses only on the behaviour of s-commerce purchasers. Regarding the demographic distribution of population and the sample design, the authors referred to reports of the Kosovo Agency of Statistics (Krasniqi et al, 2018) and Albania Institute of Statistics (2019). After data gathering, 721 valid questionnaires from Kosovo and Albania were used for further analysis.…”
Section: Data Collection Procedures and Research Methodologymentioning
confidence: 99%
“…Despite this attitude of neglect, multiple studies around the globe are bringing out the relevance of a strategic approach to the management of SMEs. A study conducted in Kosovo revealed that strategic management is of extreme importance to SMEs in the economy (Krasniqi, 2018). Gavurova et al (2020) on their part, without disputing the relevance of a strategic approach to the management of SMEs go further by calling for national as well as international benchmarks to be set to promote the use of strategic approach to the management of this category of businesses.…”
Section: Smes and Strategymentioning
confidence: 99%